2020
DOI: 10.1186/s13104-020-05059-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between severity of liver steatosis and metabolic parameters in a sample of Iranian adults

Abstract: Objectives: This study aimed to examine the relationship between severity of liver steatosis and metabolic parameters in a sample of Iranian adults. In this cross-sectional study, a total of 95 subjects aged > 20 years newly diagnosed with NAFLD were recruited. NAFLD was diagnosed using ultrasonography by a single expert radiologist in a fasting state. Results: The mean age of the patients was 49.27 (SD 9.7) years, with 53.68% males and 46.32% females. Most patients had grade I NAFLD (72.63%), 25.26% were grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…The prevalence of non‐alcoholic fatty liver disease (NAFLD) is increasing worldwide 1 . The disease can range in spectrum from simple steatosis to non‐alcoholic steatohepatitis (NASH), characterised by hepatic fat accumulation with inflammation, which can progress to fibrosis, cirrhosis and finally hepatocellular carcinoma 2,3 . According to a recent meta‐analysis, the global prevalence of NAFLD is reported to be 25.24%, with greatest prevalence in the Middle East and South America and lowest in Africa 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of non‐alcoholic fatty liver disease (NAFLD) is increasing worldwide 1 . The disease can range in spectrum from simple steatosis to non‐alcoholic steatohepatitis (NASH), characterised by hepatic fat accumulation with inflammation, which can progress to fibrosis, cirrhosis and finally hepatocellular carcinoma 2,3 . According to a recent meta‐analysis, the global prevalence of NAFLD is reported to be 25.24%, with greatest prevalence in the Middle East and South America and lowest in Africa 4 .…”
Section: Introductionmentioning
confidence: 99%
“…2,5,6 NAFLD is characterized by an atherogenic lipid profile including increased TG, lowdensity lipoprotein cholesterol (LDL-C), and very lowdensity lipoprotein cholesterol (VLDL-C) concentrations and a reduced high-density lipoprotein cholesterol (HDL-C) level leading to a significantly increased risk TUOMS P R E S S of cardiovascular disease (CVD). [7][8][9] It has also been suggested that total cholesterol (TC)/HDL-C, LDL-C/ HDL-C, and TG/HDL-C ratios are better mirror of the metabolic and clinical interactions between lipid fractions and have higher predictive values than isolated parameters used independently in disease states. 10 Furthermore, non-HDL-C which reflects all of the major lipoproteins associated with a higher risk of CVD may better identify abnormal lipid profile in patients with NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD is associated with a highly atherogenic lipoprotein profile, characterized by high serum TG, low-density lipoprotein (LDL-C), and apolipoprotein B (ApoB) concentrations and a low HDL-C concentration [ 7 , 8 ]. In addition, previous studies have shown that hypertriglyceridemia is one of the risk factors for NAFLD [ 9 ], and that the prevalence and degree of hypertriglyceridemia significantly correlate with the severity of NAFLD [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%